Analysis of the Safety of Pegfilgrastim Addition in Bleomycin, Etoposide, and Cisplatin Treatment Patients With Germ Cell Tumors - Nakagawa, Ryunosuke; Iwamoto, Hiroaki; Makino, Tomoyuki; Kadomoto, Suguru; Yaegashi, Hiroshi; Iijima, Masashi; Kawaguchi, Shohei; Nohara, Takahiro; Shigehara, Kazuyoshi; Izumi, Kouji; Kadono, Yoshifumi; Mizokami, Atsushi (Frontiers in Oncology, 2022)
It has been reported that chemotherapy drugs and granulocyte colony-stimulating factor (G-CSF) administered on the same day can aggravate neutropenia. In the present study, we investigated the safety of pegfilgrastim during bleomycin, etoposide, and cisplatin (BEP) therapy. This single-center retrospective study, including 137 cycles of BEP therapy for germ cell tumors between January 2008 and April 2021, investigated safety. Short-acting G-CSF was used for 84 cycles and pegfilgrastim was used for 53 cycles. In the pegfilgrastim group, neutrophil count at nadir was significantly higher than in the G-CSF group (median 1,650/μl and 680/μl, respectively). The incidence of grade 3–4 neutropenia was significantly higher and the duration longer in the G-CSF group. Also, there was no significant difference in the incidence of febrile neutropenia. In conclusion, concomitant use of pegfilgrastim during BEP therapy did not increase neutropenia and was effective in terms of safety.